Readiness towards E-learning amongst telecenter users - Yusof, Yuhanis; Derashid, Chek; Yaakob, Mazri; Husin, Rohani (IOSR, 2013)
This paper investigates students' readiness and attitudes towards E-learning facility. Respondents involved were users of telecenters that are located in rural areas of Peninsular Malaysia. Results have shown that the students have positive attitude towards the usefulness of e-learning but ICT infrastructure may limit their interest.Based on such findings, this paper also provides insight of an intelligent user-centric e-learning portal that presents users with dynamic learning content.Each user is to be presented with content that suits their interest and capabilities.Hence, it may attract the user to maximize the usage of the learning portal.